Nanoindentation creep behavior of Cu–Zr metallic glass films - Yaqiang Wang; Jinyu Zhang; Kai Wu; Gang Liu; Daniel Kiener; Jun Sun (Materials Research Letters, 2018)
The size-dependent hardness, strain-rate sensitivity (SRS) and shear transformation zone (STZ) volume of co-sputtered Cu–Zr metallic glass films with film thickness h spanning from 1000 to 3000 nm were systematically investigated by nanoindentation creep tests at room temperature. Experimental results manifested an exceptional decrease in hardness and a monotonic increment in SRS (or a monotonic decline in STZ volume) with reducing h. The deformation mechanism could be rationalized in light of more free volume combined with smaller STZs in thinner films, which likely trigger the strain-softening behavior. Moreover, STZs and deformation-induced devitrification promote the homogeneous-like plastic flow.